ESKAPE Pathogens in Hospitalized Patients: A Comprehensive Profiling of Infections and Characteristics at Universitas Airlangga Hospital, Surabaya, Indonesia - Dinda Rachma Harlisa; Tri Pudy Asmarawati; Firman Setiawan; Pepy Dwi Endraswari (Universitas Airlangga, Surabaya, Indonesia, 2025)
Highlights This study found that ESKAPE pathogenic infections at Universitas Airlangga Hospital were dominated by Gram-negative bacteria, particularly Klebsiella pneumoniae, with sputum as the most commonly collected specimen providing valuable data for infection control strategies. Most patients exhibited significant clinical manifestations involving neurological disorders, with the respiratory system being the most affected information that may enhance the effectiveness of patient management in the hospital. ABSTRACT Background: Infections pose a significant threat in Indonesia, particularly in healthcare settings where healthcare-associated infections (HAIs) are prevalent. At a hospital in Jakarta, the prevalence of ESKAPE pathogens was reported to be 69.8%. However, detailed data on the infection profiles of these pathogens remain scarce. This underscores the importance of studying ESKAPE pathogenic bacteria to better understand their characteristics. Objective: This study aimed to determine the infection profile of ESKAPE pathogens in hospitalized patients at Universitas Airlangga Hospital, Surabaya, Indonesia in 2022. Material and Method: This descriptive observational study employed a retrospective design using secondary data from non-ICU inpatients at Universitas Airlangga Hospital infected with ESKAPE pathogens in 2022. Total sampling was applied to eligible medical records. Result: The study included 119 specimens from inpatients infected with ESKAPE pathogens that met the inclusion and exclusion criteria. Of these, 78% were Gram-negative bacterial infections, with Klebsiella pneumoniae being the most prevalent (29%). Sputum was the most commonly collected specimen (49%). Most patients were male (57%), aged 56–65 years (29%), and had no comorbidities (46%). Additionally, 63% of patients had used invasive devices during hospitalization. The majority were admitted to low-care inpatient wards. The primary clinical features were neurological complaints (29%) and respiratory disorders (37%), predominantly associated with Klebsiella pneumoniae. Conclusion: ESKAPE infections were primarily caused by Klebsiella pneumoniae, a Gram-negative bacterium, most frequently identified in sputum samples. The predominant clinical manifestations were decreased consciousness and respiratory disorders. Affected patients were mainly male, aged ≥56 years, hospitalized in low-care wards, with a history of invasive device use and no comorbidities.